The fatty acid profiles of mixed fermented milk and its anti-inflammation properties in an LPS-induced RAW264.7 cell model. Issue 5 (11th February 2022) - Yang, Guo; Lu, Qianqian; Cui, Lei; Zong, Manli; Guo, Yuxing; Liu, Lianliang; Pan, Daodong; Wu, Zhen
Abstract : Anti-inflammatory properties of fermented milk by the release of polyunsaturated fatty acids and the possibility to develop functional fermented milk with intestinal inflammation prevention properties. Abstract : Increasing knowledge of probiotics has shown that co-cultures of probiotics can achieve better fermentation and beneficial effects, and adding LAB to fermented milk fat products can increase the production of polyunsaturated fatty acids. In this study, the fatty acid profiles of milk fermented by L. reuteri DMSZ 8533, L. plantarum A3, and L. acidophilus CICC 6074 were investigated, and the strain difference on the polyunsaturated fatty acid profiles is also confirmed. The results found that L. plantarum A3 fermented milk with a mixed fermentation starter ratio of 1 : 1 : 2 could promote the hydrolysis of lipase to produce more polyunsaturated fatty acids. Furthermore, the milk fat complex hydrolyzed lipids can inhibit the expression of inflammatory factors TNF-α and IL-6 and promote the secretion of IL-10 through the MAPK-dependent NF-κB pathway. Furthermore, the anti-inflammation potential of the fatty acid profiles in the fermented milk products was also revealed in an LPS-induced RAW264.7 cell model. It is hoped that this study can shed light on the anti-inflammatory properties of fermented milk by the release of polyunsaturated fatty acids and the possibility to develop functional fermented milk with intestinal inflammation prevention properties.